Eliminação urinária prejudicada em pacientes com acidente vascular cerebral - Leandro, Telma Alteniza (2021)
Stroke is determined by the rapid development of clinical signs of focal or global disorders of brain function, with vascular origin, causing cognitive and sensorimotor changes, according to the area and extent of the brain lesion. Among these changes, urinary symptoms stand out, commonly seen in people with stroke. Therefore, the aim of this study was to clinically analyze the nursing diagnoses Impaired Urinary Elimination and Lower Urinary Tract Symptoms in patients with brain injury caused by stroke. Cross-sectional study, developed in two public hospitals of Fortaleza / CE, from October 2019 to March 2021. The sample consisted of 142 patients. Data collection was performed using a form based on the nursing diagnoses Impaired Urinary Elimination and Lower Urinary Tract Symptoms, presented by the International Continence Society and an integrative literature review. A statistical analysis was performed with support of the statistical program IBM® SPSS® version 21.0 for Windows® and the R software version 2.12.1. A descriptive analysis of the data was performed by calculation of absolute frequencies, percentages, measures of central tendency, and dispersion. The latent class model was used to determine Impaired Urinary Elimination and measures of sensitivity and specificity of clinical indicators. The research began with the consent of the proponent institution and co-participants, as well as data collection started after signing the Informed Consent Form. Most of the participants were male, with an average age of 62.18 years, coming from the state capital, retired and with an average personal income of 1,344 reais. Regarding clinical variables, ischemic stroke with LACS classification and brain involvement on the left was predominant. The changes resultant of the event were hemiparesis, hemiplegia, dysarthria, dysphagia, dysphonia, sensory, visual, and proprioception changes. The main comorbidities evidenced were diabetes, hypertension, heart problems, and dyslipidemia. The prevalence of Impaired Urinary Elimination was 32.38% among participants. The most prevalent indicators were Nocturia and Urinary Urgency. Nocturia was the clinical indicator with the greatest sensitivity for that diagnosis. Urinary Incontinence, Dysuria, Urinary Urgency, Frequent urination, and Hesitation showed high values of sensitivity. In addition, the variable female gender had a statistically significant relationship with that diagnosis. The prevalence of Lower Urinary Tract Symptoms was 79.12%, and the most prevalent indicators were Nocturia, Sensation of Bladder Filling, Urinary Urgency, Terminal Dribble and Urinary Retention. The presence of Sensation of Bladder Filling was the symptom that presented high values of sensitivity and specificity. Post Micturition Dribble, Position-Dependent Urination, Dysuria, and Intermittency have high specificity values among the investigated urinary symptoms. The most frequent types of urinary incontinence were urge, functional, and stress incontinence. Regarding the diagnosis of Urinary Retention, the most evident clinical manifestations were Sudden Inability to Urinate, Sensation of Filling of the Bladder, Distension of the Bladder, and Dysuria. It is considered that the present study provided the clinical profile of Impaired Urinary Elimination in the population with stroke.